Pengaruh Pengungkapan Environmental, Social Dan Governance Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Sektor Non-Keuangan Yang Terdaftar Di Bei Periode 2021-2022) - Siti Sugiarti Labaco; Mutiara Ahmad Pabulo, Azfa (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
Abstrack: The aim of the research is to analyze the influence of social, governance and environmental disclosure on the financial performance of non-financial companies. These three factors are measured using standard GRI index metrics, with financial performance as the dependent variable measured by ROA. Method: Quantitative data using a purposive sampling approach was used in the research, selecting 35 companies from the non-financial sector for the 2021-2022 period, thus obtaining 70 survey data samples. Multiple regression analysis method as a hypothesis test. Results: (1) ENV disclosure has no partial effect on the financial performance of the non-financial sector, with a sig value of 0.470 > 0.05. (2) SOC disclosure also has no partial effect on the financial performance of the non-financial sector, with a sig value of 0.725 which is > 0.05. (3) GOV disclosure does not show a partial influence on the financial performance of the non-financial sector, with a sig. 0.039 > 0.05.Conclusion: Based on partial test results, it shows that there is no significant influence between environmental, social and governance (ESG) disclosure variables on company financial performance in the non-financial sector. Keywords: Financial Performance, Environmental, Social, Governance, Company